Fluxos de fósforo em uma bacia hidrográfica sob cultivo intensivo no sul do Brasil - Scotto, Marco Antônio Lenz (2014)
Eco-environments from sweet water are crucially important, as they provide water for multiple purposes, including human and animal consumption, irrigation and entertainment. However, its quality can suffer significant alterations due to anthropogenic interventions capable to elevate phosphorous (P) level in water and sediments. Due to phosphorus mobilization by erosive processes, it can be carried into the rivers and accumulate up to critical levels leading to malefic effects. Therefore, the purpose of this research was to describe the spatial and temporal variability of phosphorus flow in Guaporé river watershed, with high variability of use and management of soil and relief. Samples from natural flow water, suspended sediments and the ones deposited into the water course bed were collected from December of 2012 to September of 2013. Total concentration of phosphorus (PT) ranged from 403,4 to 2752,8mg kg-1 in suspended sediments and from 513,4 to 1.566,9 mg kg-1 in the bed sediments. Total Phosphorus ranged from 0,010 to 0,543 mg L-1 in the water samples. Organic carbon (COT) ranged from 2,11 to 7,83% in suspended solids and from 1,5 to 4,1% in the bed sediments. In sazonal patterns, the study demonstrated that agricultural sites with conventional planting and influenced by urban environments export significantly higher concentrations of suspended sediments and total phosphorus than natural control (forest).